Peningkatan Pemberdayaan Masyarakat Melalui Usaha Rumahan Abon Ikan di Desa Tambu - Dinnita Azhar Lembah; Muhammad Din; Faruq Lamusa (Jurnal Nusantara Berbakti, 2023)
The economic conditions in Tambu village cannot be separated from the potential for natural resources that can support the process of improving people's welfare, this can be seen from the area of sea waters in Tambu village. This is what supports the people of Tambu village to make a living as fishermen. The abundant potential is in the form of marine products, namely Katombo fish, the people of Tambu village generally work as fishermen, they get their catch and then sell it directly to the community or to the market without processing the catch they get, lack of public knowledge in innovating the catch they get . Therefore, it is important to increase empowerment to increase the potential and abilities possessed by individuals or communities by producing home-based business products from existing potential, namely processing shredded katombo fish as an effort to utilize fish catches into products that have economic value. So that Tambu Village is an example for other villages in Central Sulawesi, especially Donggala Regency.